(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Vyshnevska K. A set of exercises for the formation of communicative skills in the professional-oriented foreign language teaching future professionals in economics. The article considers the content, typology, and the principles on which set of exercises experimental program professionally-oriented foreign language teaching future professionals of the economy is based.